2019
DOI: 10.1186/s13104-019-4731-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholera hotspots and surveillance constraints contributing to recurrent epidemics in Tanzania

Abstract: ObjectiveWe described the dynamics of cholera in Tanzania between 2007 and 2017 and assessed the weaknesses of the current surveillance system in providing necessary data in achieving the global roadmap to 2030 for cholera control.ResultsThe Poisson-based spatial scan identified cholera hotspots in mainland Tanzania. A zero-inflated Poisson regression investigated the relationship between the incidence of cholera and available demographic, socio-economic and climatic exposure variables. Four cholera hotspots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…These differences could result from the fact that we used data for a longer time period (10 years) with rigorous statistical methods and ignored mean annual incidence ≤ 2 cases per 100 000 people while the desk review data spanned six years using mean annual incidence of 1 case per 100 000 inhabitants. As we found in this study, SaTScan has been widely used and found very helpful in identification and classification of cholera clusters (hotspots) to inform intervention measures in SSA including Cameroon [ 17 ], Uganda [ 18 ], Zambia [ 46 ], and Tanzania [ 47 ]. However, the GTFCC method is relatively new and we found no evidence of its use in published reports.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could result from the fact that we used data for a longer time period (10 years) with rigorous statistical methods and ignored mean annual incidence ≤ 2 cases per 100 000 people while the desk review data spanned six years using mean annual incidence of 1 case per 100 000 inhabitants. As we found in this study, SaTScan has been widely used and found very helpful in identification and classification of cholera clusters (hotspots) to inform intervention measures in SSA including Cameroon [ 17 ], Uganda [ 18 ], Zambia [ 46 ], and Tanzania [ 47 ]. However, the GTFCC method is relatively new and we found no evidence of its use in published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Les aires de santé de l'axe lac Tanganyika sont quasiment les seules contributrices des cas de choléra, surtout celle de Moba-Port. La proximité avec le lac Tanganyika et le recours à ses eaux pour l'alimentation et l'usage domestique constituent des facteurs de risque importants, comme le souligne Shapiroet al [29], Taylor et al [9], Hounmanouet al [30] et Bompangweet al [10] concernant les lacs Victoria, Nyasa et Tanganyika. Il a été constaté que plus on s'éloigne du lac, la notification des cas de choléra dans le système de surveillance des maladies devient nulle.…”
Section: Resultatsunclassified
“…A few countries in Africa including Zimbabwe and Ghana have investigated the temporal trends and the nature of spatial interaction of cholera (Ngwa et al, 2016; Osei & Stein, 2018; Luque Fernandez et al, 2012). Furthermore, studies on spatio-temporal trend of cholera have been extensively done in Cameroon, Uganda, Zambia, and Tanzania to identify cholera clusters and provide valuable insights for implementing intervention measures (Mwaba et al, 2020; Hounmanou et al, 2019; Bwire et al, 2017; Ngwa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%